Medial Deviation of a 6° Prosthetic Trochlear Groove After Kinematically Aligned Total Knee Arthroplasty Occurs in Four Types of Coronal Plane Alignment of the Knee (CPAK) and Decreases the Forgotten Joint Score - Dragan V. Jeremic, MD; Johan Bellemans, MD, PhD; Elliot Sappey-Marinier, MD, PhD; Stephen M. Howell, MD; Werner Hettwer, MD; Maury L. Hull, PhD (Arthroplasty Today)
Background: The study focused on kinematically aligned total knee arthroplasty (KA TKA). It identified which coronal plane alignment of the knee (CPAK) types are associated with a higher proportion of medial deviation of the 6° prosthetic trochlear groove (PTG) relative to the quadriceps’ line of pull and whether medial deviation adversely affected the Forgotten Joint Score (FJS). The research calculated the minimum PTG angle required to prevent medial deviation by at least 2° in all patients. Methods: The study analyzed 296 KA TKAs with a postoperative long-leg scanogram and a 2-year FJS score. Radiographic measurements were used to determine the CPAK type and to identify the deviation of the 6° PTG relative to the quadriceps’ line of pull as medial (−) or lateral (+). Results: Fifty-one percent of KA TKAs had a medial deviation of the PTG, and the proportion was higher in CPAK I, II, III, and VI than in IV and V types (P < .05). The median FJS of CPAK III was significantly lower than I and IV (P < .0262) and comparable to II, V, and VI (P > .085). The minimum PTG angle required to prevent medial deviation by at least 2° in all patients is 17°. Conclusions: A medial deviation of the 6° PTG occurred in more than half of the KA TKAs and was observed in 4 of 6 CPAK types. Because medial deviation was associated with a lower FJS, it is suggested that the femoral component should have a minimum PTG of 17° to prevent medial deviation by at least 2° in all patients. Level of evidence: IV.